COVID-19: Accrual Earnings Management Practices in Pharmaceutical Companies in Indonesia - Widyaningsih Azizah; Hotman Fredy; Fathoni Zoebaedi (UNIB Press, 2022)
The COVID-19 pandemic has disrupted the supply chain of domestic pharmaceutical raw materials, where 95% of the fulfillment of raw materials relies on imports. Amid difficulties in meeting raw materials, the pharmaceutical sub-sector companies have become one of the sectors of choice for investors throughout 2020, in line with the sentiment of the COVID-19 pandemic. As one of the prima donnas’ sectors during pandemic, financial reports presented by pharmaceutical sector should report the actual condition of the company. This study aims to empirically examine the differences in accrual earnings management before and after the COVID-19 pandemic in pharmaceutical sub-sector companies in Indonesia. To evaluate changes in accrual earnings management in the period before the COVID-19 pandemic, namely in 2019 and after the COVID-19 pandemic, namely in 2020, the Paired Sample T-test was used. The findings of this study show that there is no average difference between accrual earnings management before COVID-19 (Pre-test) and after COVID-19 (Post-test), indicating that COVID-19 has no impact on earnings management practices in the pharmaceutical sub-sector companies in Indonesia. The deteriorating global economic conditions caused by the COVID-19 pandemic do not necessarily encourage managers to carry out aggressive earnings management. The pharmaceutical sub-sector companies that have become the center of attention of investors during this pandemic, as a result the company’s performance shown in the financial statements does not make managers aggressively try to manipulate their financial statements.